Distinct ZIKV strain signatures and type I IFN modulation reveal a protective role of brain endothelial interferon signaling in vitro and in vivo - Lima, Luan Rocha; Mustafá, Yasmin Mucunã; Fonseca, Paula Luize Camargos; Coelho, Sharton Vinícius Antunes; Parisi, Pierina Lorencini; Simeoni, Camila Lopes; Meuren, Lana Monteiro; Bezerra, Bruno Braz; Mebus-Antunes, Nathane Cunha; Matassoli, Flavio; Proença-Modena, Jose Luiz; Aguiar, Renato Santana; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionZika virus (ZIKV) infection has been associated with neurological syndromes, particularly during outbreaks caused by Asian lineage strains. However, experimental models suggest that African strains may exhibit an equal or more virulent profile. Neuroinvasion by systemic viruses often requires crossing the blood–brain barrier (BBB), which disruption amplifies viral dissemination and neuropathology. Type I interferons (IFNs) are key to restricting ZIKV replication, but their specific role in preserving BBB integrity remains poorly defined.MethodsHere, we used human brain microvascular endothelial cells (HBMECs) as a simplified BBB model to compare transcriptional responses and IFN modulation following infection with either the African prototype strain ZIKVMR766 or the Asian epidemic strain ZIKVPE243. The role of endothelial cell–mediated IFN responses was further assessed in vivo by intravascular inoculation of mice with endothelial-specific IFNAR depletion using ZIKVMR766.Results and discussionInfection of HBMEC with ZIKVMR766 triggered a greater number and broader range of differentially expressed genes, especially ones associated with interferon signaling and translational pathways, whereas ZIKVPE243-infected samples clustered closer to non-infected ones. ZIKVMR766 infection also resulted in higher viral titers and faster dissemination across endothelial monolayers. Both strains induced IFN-β expression but suppressed downstream IFN signaling by reducing STAT1 phosphorylation and promoting STAT2 degradation, with these effects being more pronounced for ZIKVMR766. Despite these evasion mechanisms, neutralization assays revealed that endothelial cells-derived IFNs production and response partially restricted viral replication, preserved HBMEC viability, and protected against barrier disruption, with ZIKVPE243 showing greater sensitivity to IFN-β. Importantly, in vivo infection of mice lacking endothelial IFNAR signaling resulted in elevated CNS viral load and increased lethality following ZIKVMR766 infection, underscoring the pivotal role of endothelial IFN responses in viral control, maintenance of BBB integrity, and protection against neuroinvasion.